A METHOD FOR GRAPHICALLY PRESENTING THE DEFORMATION MODULUS OF JOINTED ROCK MASSES - Li C. (My University, 2001)
The deformability of jointed rock masses is associated with the elastic properties of the intact rocks as well as the geometric structure and the stiness of the geo- logical discontinuities within the rock masses. Determination of the deformation modulus of a rock mass is always a problem in practice. The conventional means to determine the deformation modulus is to perform in-situ tests, for instance dilatometer tests, plate-loading tests, flat-jack tests and block tests (Franklin and Dusseault, 1989; Yow Jr., 1993). One can question whether a single evaluation of the deformation modulus obtained in in-situ tests is representative of the whole rock mass, considering the relatively small volume of the tested sample and the orientation-related properties of the discontinuities in the rock mass. In-situ tests are time-consuming and very costly, so that empirical approaches are more often employed today for estimation of the deformation modulus of rock masses, for instance the methods developed on the basis of rock mass classification systems by Bieniawski (1978), Serafim and Pereira (1983) and Barton et al. (1980). The deformation modulus of a jointed rock mass may be estimated using the geometric data of the rock joints as well as the elastic parameters of the intact rocks and the rock joints if available. Analytical studies have been made on this subject by a number of researchers, for example Fossum (1985), Amadei (1993) and Huang et al. (1995). Amadei (1993) presented a general solution to the deformability of regularly jointed rock masses. His work shows that the deforma- tion modulus is anisotropic in jointed rock masses. The structure and the stiness of the rock joints predominately determine the magnitude of the deformation modulus of the rock mass. In Amadei's approach, the regularly jointed rock mass is replaced by an equivalent orthotropic continuum. This note introduces a method to present the deformation modulus of jointed rock masses in a hemispherical projection. It is assumed in this approach that the